2013
DOI: 10.1093/jjco/hyt116
|View full text |Cite
|
Sign up to set email alerts
|

Poorer Survival of Male Breast Cancer Compared with Female Breast Cancer Patients May Be Due to Biological Differences

Abstract: Objective: The objective of the study was to compare disease-free survival and overall survival in a group of matched males and females with breast cancer, and to analyze possible treatment-and gender-related differences. Methods: We retrospectively analyzed the data of 150 operable male breast cancer patients treated in our hospital from December 1980 to June 2012. Each male breast cancer patient recorded in the database was matched with two female breast cancer patients of equal stage. Prognosis in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
5
27
0
Order By: Relevance
“…HR status did not significantly affect OS in our cohort, which concords with other reports where HR positivity was more highly expressed than in our patients [2,3,15]. Giordano and coworkers reported a 5.7% negative estrogen receptor status in their cohort, with a 5-year survival of 64%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…HR status did not significantly affect OS in our cohort, which concords with other reports where HR positivity was more highly expressed than in our patients [2,3,15]. Giordano and coworkers reported a 5.7% negative estrogen receptor status in their cohort, with a 5-year survival of 64%.…”
Section: Discussionsupporting
confidence: 86%
“…Prognostic factors for MBC are mostly studied in retrospective investigations with small samples. Men with breast cancer reportedly have poorer outcomes than matched women patients, even at the same disease stages, which might be because of variations in tumor biology between male and female patients [3]. Ethnic differences might also affect the prognosis of MBC [4].…”
Section: Introductionmentioning
confidence: 99%
“…After controlling for important prognostic factors, we described a worse survival to MBC patients that are similar to other studies, present however, a lower 5‐year overall survival (65.2%) compared to some authors that reported >80% . This could be probably explained by the selection of our population that only contains patients that recurred and because of that have a poor prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…Male breast cancer (MBC) is a rare disease, accounting for <1% of all breast cancer cases . Recently and due to the increase in its incidence, some studies were published suggesting a worst outcome for male compared to female breast cancer (FBC) patients, justified by: comorbid conditions and delay in the diagnosis in male patients, different age and stage at diagnosis or even differences in tumors biology …”
mentioning
confidence: 99%
“…These biological differences could potentially impact on clinical prognosis. A recent study by Chen et al 18 stated that male breast cancers had poorer survival outcomes when compared to female breast cancers, which may be attributed to their biological differences.…”
Section: Discussionmentioning
confidence: 99%